BALLISTIC IMPACT BEHAVIOR OF WOVEN FABRICS POLYMER COMPOSITES WITH DIFFERENT STRUCTURES AND CONFIGURATIONS - Satoto, Rahmat; Nugroho, Pramono; Santosa, Tata (LIPI Press, 2009)
This study reports the ballistic penetration performance of a composite materials composed of woven Kevlar fabric, woven nylon fabric, woven ramie fabrics impregnated with compatible resins and hybrid composite construction of these three structures. The composite panels were tested by low velocity bullet (around 322 m/s) in incident angle of 0o according to level I NIJ 0101.04. The effects of fabric configuration, composite structure, and the resin compatibility on ballistic performance were investigated. Composites with Kevlar-A363F fabric performed the best among these composites. Composite of 4 layers kevlar-A363F shows the better performance than 32 layer composites of nylon- oxford X7 and 48 layers ramie fabrics. Ballistic penetration mechanism of the fabric-reinforced composites demonstrated that breakage, matrix cracking, and delamination are three typical mechanisms of failure and energy absorption. In the kevlar-A363F composites, ballistic impact causes the blunting of a projectile. This projectile deformation is seen as an effective mechanism of energy absorption. Kinetic energy of a blunt projectile will be absorbed by wider cross section of the next fabric layer, so the projectile velocity slows down until it stops. The enhancement of ballistic performance is shown to be associated with the fiber strength, construction, fabric configuration, and matrix compatibility. It is likely that the best design of bullet proof composite can be identified.